Programmatic advertising and consumer attitudes in online retailing - Yli-Kuivila, Le (2023)
Programmatic advertising (PA) has gained its popularity in the field of marketing. According to the literature review, there has been various studies about PA’s characteristics and exploring PA from business’s perspective. Research has also created a link between the PA and metaverse since metaverse has largely been considered as a new digital advertising channel and medium through which brands can connect with customers. However, there are dearth studies about PA’s effect on consumers. Therefore, this study aims to contribute to the aforementioned research gap so that consumer’s perspective about PA-empowered ads can be brought to light and how it leads to their correspondent behaviours such as intention to purchase and ad avoidance.